2000
DOI: 10.1053/he.2000.6253
|View full text |Cite
|
Sign up to set email alerts
|

Host genetic factors influence disease progression in chronic hepatitis C

Abstract: Progressive hepatic fibrosis and cirrhosis develops in 20% to 30% of patients with chronic hepatitis C virus (HCV). We propose that host genetic factors influencing fibrogenesis may account for some of the variability in progression of this disease. In progressive fibrosis of other organs, particularly heart and kidney, production of the profibrogenic cytokine, transforming growth factor β1 (TGF‐β1), may be enhanced by angiotensin II, the principal effector molecule of the renin‐angiotensin system. The inherit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
280
5
12

Year Published

2001
2001
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 376 publications
(308 citation statements)
references
References 32 publications
(35 reference statements)
10
280
5
12
Order By: Relevance
“…Several recent studies suggested that IL10 polymorphisms may influence HCV outcome in the host [38][39][40][41]49 while others have not found associations. 42,43 Generally, these are concentrated on the proximal IL10 promoter polymorphisms that have been associated with the differential IL-10 expression, 46,50 while other polymorphisms, particularly those in the distal part of the promoter, have also been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies suggested that IL10 polymorphisms may influence HCV outcome in the host [38][39][40][41]49 while others have not found associations. 42,43 Generally, these are concentrated on the proximal IL10 promoter polymorphisms that have been associated with the differential IL-10 expression, 46,50 while other polymorphisms, particularly those in the distal part of the promoter, have also been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that have looked at outcome of disease have found no association with TNF SNPs. 104,[111][112][113][114][115] However, two studies have appeared that did find an association of TNF SNPs with HCV. 116,117 The latter study 117 is curious not because of the reported higher occurrence of the À238A allele among chronic HCV patients, but because the reported frequency in a healthy control group (n ¼ 99) drops from 7 117 to 3.5% in an article published concurrently by the same group.…”
Section: Leprosymentioning
confidence: 99%
“…Some evidence for the involvement of host genetic factors in the outcome of HCV infection exists. [13][14][15] Antiviral therapy of CHC with pegylated interferon alfa-2a or -2b and ribavirin yields HCV eradication rates from 54 to 56% 16,17 and sustained response might diminish fibrosis. 18 However, antiviral therapy carries substantial morbidity at high costs.…”
Section: Introductionmentioning
confidence: 99%